2010
DOI: 10.1159/000321133
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Partial Remission of Metastatic Pancreatic Cancer Following Systemic Chemotherapy with Gemcitabine and Oxaliplatin plus Adjunctive Treatment with Mistletoe Extract

Abstract: Background: The clinical prognosis of metastatic pancreatic cancer is very poor, with a median survival time of such patients ranging from 3 to 6 months. Current chemotherapy regimens include the combination of oxaliplatin and gemcitabine. Case Report: A 43-year-old woman was diagnosed with pancreatic adenocarcinoma spreading into the regional lymph nodes and into multiple liver segments (pT3, pN1, pM1). Upon diagnosis, she underwent a pylorus-preserving pancreatic head resection, including dissection of regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…25,26,28,29 As for clinical use, several groups have published case studies describing partial or complete tumor remission by IT mistletoe therapy alone or in combination with conventional therapies. [30][31][32][33] A recent retrospective study by Schad et al, 34 which included 39 pancreatic patients who received a total of 223 IT mistletoe injections in addition to conventional therapies, suggests that IT applied mistletoe might have contributed to an improved overall survival. Prospective clinical studies designed to confirm efficacy for IT or multimodal mistletoe therapy are therefore required.…”
Section: Introductionmentioning
confidence: 99%
“…25,26,28,29 As for clinical use, several groups have published case studies describing partial or complete tumor remission by IT mistletoe therapy alone or in combination with conventional therapies. [30][31][32][33] A recent retrospective study by Schad et al, 34 which included 39 pancreatic patients who received a total of 223 IT mistletoe injections in addition to conventional therapies, suggests that IT applied mistletoe might have contributed to an improved overall survival. Prospective clinical studies designed to confirm efficacy for IT or multimodal mistletoe therapy are therefore required.…”
Section: Introductionmentioning
confidence: 99%
“…Ritter et al described the case of a woman aged 43 who had undergone a pancreatic head resection plus nine cycles of palliative treatment with gemcitabine plus oxaliplatin, and concomitant treatment with mistletoe. Ten months later, the patient was free of any evidence of tumor progression [21].…”
Section: Mistletoementioning
confidence: 93%
“…Oxaliplatin and gemcitabine are the standard chemotherapy to combat the cancer. Ritter et al (2010) investigated the adjunct therapy possibilities with mistletoe extract. In a case study, 37 weeks after surgery, the patient demonstrated a sustained partial remission, and the chemotherapy was stopped.…”
Section: Synergistic Effectsmentioning
confidence: 99%